Spirit Pengembangan Sumber Daya Manusia Berwawasan Islam Multikultural Pada Sekolah Berprestasi (Studi Di Sma Karangturi Semarang): (STUDI DI SMA KARANGTURI SEMARANG) - Ali Ismunadi; Maskuri Bakri; Moh. Faishol Khusni Khusni (INOVATIF: Jurnal Penelitian Pendidikan, Agama, dan Kebudayaan, 2021)
This research aims to describe the spirit and the model of human resource development with multicultural insight in general and specifically the development of multicultural Islam at SMA Karangturi Semarang which is also known as a school with a full of achievements. This research use descriptive qualitative approach where data is collected through observation, interview and documentation techiques. These findings indicate that schools create an environment and a school system that promotes the beauty of a harmonious life in terms of ethnic and religious differences. Related to the PAI learning process, PAI teacher is carrying out a creative and contextual learning process. In this context, the teacher has an important role as a represntative role model to represent the values of multicultural Islamic education through giving real examples from teachers, how to live with mutual respect and build good cooperation between students of different ethnicities and religions and how to maintain good relations with the community. Regarding Islamic learning for Muslim students, they also get the same learning process even though they are a minority part of the school. The development of superior school resources with a multicultural Islamic education spirit in SMA Karangturi consists of input (school support with a systematic and regular multicultural environmental conditioning design), processes (learning, school programs, collaboration with communities and exemplary teachers), and output (students with multi-participant character, high achievement and high sensitivity and empathy towards society).